2019
DOI: 10.3389/fgene.2019.00236
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Interrogation of Cancer Omics to Identify Subtypes With Significant Clinical Differences

Abstract: Recent advances in high-throughput sequencing have accelerated the accumulation of omics data on the same tumor tissue from multiple sources. Intensive study of multi-omics integration on tumor samples can stimulate progress in precision medicine and is promising in detecting potential biomarkers. However, current methods are restricted owing to highly unbalanced dimensions of omics data or difficulty in assigning weights between different data sources. Therefore, the appropriate approximation and constraints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…In particular, Koh et al (44) predicted breast cancer subtypes by applying a modified shrunken centroid method in the development of their networkbased tool, iOmicsPASS. Further, breast cancer datasets in TGCA represent a benchmark for integrative models (92)(93)(94), as well as AML (95). More recently, the success of deep learning algorithms in various bioinformatics fields (96) prompted the adoption of deep neural networks for omics-integration in precision oncology.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In particular, Koh et al (44) predicted breast cancer subtypes by applying a modified shrunken centroid method in the development of their networkbased tool, iOmicsPASS. Further, breast cancer datasets in TGCA represent a benchmark for integrative models (92)(93)(94), as well as AML (95). More recently, the success of deep learning algorithms in various bioinformatics fields (96) prompted the adoption of deep neural networks for omics-integration in precision oncology.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In particular, Koh and colleagues (41) predicted breast bioRxiv INF cancer subtypes by applying a modified shrunken centroid method in the development of their networkbased tool, iOmicsPASS. Further, breast cancer datasets in TGCA represent a benchmark for integrative models (87,88,89), as well as AML (90). More recently, the success of deep learning algorithms in various bioinformatics fields (91) prompted the adoption of deep neural network for omics-integration in precision oncology.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Besides the deep learning methods to predict the mirna-targets, there are other method to be used for the similar task [21]. Also, it has been shown that the finding such regulatory relationship can be used for cancer subtyping [24]. Because of not fully understood rules that govern miRNAs targeting process and different training datasets for different algorithms, there is limited overlap between the targets that are predicted by various programs.…”
Section: Introductionmentioning
confidence: 99%